Genetic Diversity Study Among Six Genera of Amaranth Family Found in Malang Based on RAPD Marker - Fatinah, Arik Arubil; Arumingtyas, Estri Laras; Mastuti, Retno (Journal of Tropical Life Science, 2012)
Genera of amaranth family tend to have phenotypic variation partly caused by environmental factor. Phenotypic variation was the result of interaction between genetic and environmental factors. One of molecular markers that is widely used for detecting genetic variation is RAPD. RAPD is used for polymorphism detections and is now possible for identifiying a large number of loci and ascribes unambiguous taxonomic and genetic relationships among different taxa. Members of amaranth family found in Indonesia are Amaranthus, Celosia, Aerva, Alternanthera, Achyranthes, Gomphrena, Salsola, and Iresine. Six genera of which (Amaranthus, Celosia, Aerva, Alternanthera, Achyranthes, and Gomphrena) were observed in this study. DNA was extracted from fresh young leaves using Doyle and Doyles method with modification in the extraction buffer used. RAPD analyses were carried out with 20 decamer primers from Kit A of Operon Technology. DNA was amplified using master cycler gradient Eppendorf with 35 cycles. RAPD products were separated on 1,5 % agarose gels and detected by staining with ethidium bromide. There were 374 bands generated in 18 random primers. The number of monomorphic bands, polymorphic bands, and the percentage of polymorphism were 21 bands, 353 bands, and 94,38 % respectively. The high number and percentage of polymorphic bands revealed genomic DNA variation. This variation is in accordance with phenotypic variation detected in this experiment. Therefore, it can be concluded that, based on DNA polymorphism detected by RAPD, Amaranth family can be classified into two sub families namely Amaranthoideae and Gomphrenoideae.